Pendampingan Pelaksanaan Wadiah Qurban di Bank Mini Syariah Auliaurrasyidin - Selviani Selviani; Saiin Saiin; Veni Lestari; Erma Susanti; Deddy Yusuf Yudhyarta (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Wadiah qurban BMS Auliaurrasyidin is a type of deposit that is allocated for the preparation of the customer's qurban worship funds. Wadiah qurban BMS Auliaurrasyidin is carried out collectively, this activity is a form of community service and the implementation of sharia banking contracts. The reason for the importance of this activity is to educate students regarding the organization and slaughter of sacrificial animals The research method used is the field method, where the stages of qurban activities consist of pre-implementation, namely the preparation stage, then the implementation stage, namely the slaughtering process and post-implementation or distribution and delivery of qurban meat. The qurban worship committee consists of 10 people and 7 customers or qurban participants with the number of animals slaughtered 1 cow with 83.6 kg of clean meat and 109 coupons are allocated for the qurban beneficiaries.